Clima escolar y desempeño académico en los estudiantes de la Unidad Educativa Particular “Liceo Nuevo Mundo - Tene Usca, Wendi Nicol (2023)
The objective of this research work was to determine the influence of the school climate on the academic performance of the students of the Unidad Particular Educativa "Liceo Nuevo Mundo" because the development of the students is reflected in the coexistence with their peers, the interpersonal relationships between classmates in the classroom, which is made up of part of a psychosocial process generating well-being in students, where they share and connect their ideas with others in order to establish socio-affective links, the research was supported with information from primary sources and the contribution of the researchers with criteria according to reality. The methodology used corresponds to a qualitative approach with an ethnographic design. The type of research for the objective is essential; for the place, it is field research; the study type is cross-sectional. The sample was non-probabilistic and intentional and consisted of 133 students corresponding to Básica Media level, Básica Superior level and Baccalaureate and nine teachers from the Unidad Particular Educativa "Liceo Nuevo Mundo." The techniques used were observation with its instrument, the observation sheet for the school climate with its dimensions in the teacher-student relationship; student– student; ecology in the classroom; student-curriculum-teacher relationship; and for academic performance, the survey with a questionnaire of questions based on selfefficacy, motivation, essential learning, and the qualitative and quantitative grading scale. The analysis of the information and the interpretation of the data it was carried out with the techniques suggested in the approach according to the instruments applied, such as the observation sheet and the questionnaire for the data processing, objectivity was used with the Excel program, complemented with the elaboration of graphical representation statistics such as tables and diagrams, of the analysis of each question, reflected in the survey, thus being the results obtained globally according to the participation of teachers and students.